Species identification and likely catch time period of whale bones from South Georgia. Issue 1 (30th April 2014) - Sremba, Angela L.; Martin, Anthony R.; Scott Baker, C.
Abstract Skeletal remains of baleen whales killed during the onset of 20th century commercial whaling lie scattered across the shores and abandoned whaling stations of the subantarctic island of South Georgia. Here we report on genetic species identification of whale bones collected from South Georgia using standard historical DNA protocols. We amplified and sequenced short fragments of the mitochondrial DNA (mtDNA) control region from 281 available bone samples. Of these, 231 provided mtDNA sequences of sufficient quality and length (174–194 bp) for species identification: 158 bones were identified as humpback whale (Megaptera novaeangliae), 51 bones were identified as fin whale (Balaenoptera physalus), 18 bones were identified as blue whale (B. musculus), two bones were identified as sei whale (B. borealis), one bone was identified as a southern right whale (Eubalaena australis), and one bone was identified as a southern elephant seal (Mirounga leonina). The prominence of humpback, fin, and blue whale bones in the sample collection corresponds to the catch record of the early years of whaling on the island of South Georgia (pre‐1915), prior to the depletion of these populations.